2018
DOI: 10.3390/su10041031
|View full text |Cite
|
Sign up to set email alerts
|

Social Life Cycle Approach as a Tool for Promoting the Market Uptake of Bio-Based Products from a Consumer Perspective

Abstract: Abstract:The sustainability of bio-based products, especially when compared with fossil based products, must be assured. The life cycle approach has proven to be a promising way to analyze the social, economic and environmental impacts of bio-based products along the whole value chain. Until now, however, the social aspects have been under-investigated in comparison to environmental and economic aspects. In this context, the present paper aims to identify the main social impact categories and indicators that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…Last but not least, we realized that for any product or service, regular LCA practice does not take into account economic and social factors. In this context, researchers have been dedicated to the integration of economic models as well as ecological and social theories [31][32][33][34]. Nowadays life cycle sustainability assessment (LSCA) has been developed rapidly because of its comprehensiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, we realized that for any product or service, regular LCA practice does not take into account economic and social factors. In this context, researchers have been dedicated to the integration of economic models as well as ecological and social theories [31][32][33][34]. Nowadays life cycle sustainability assessment (LSCA) has been developed rapidly because of its comprehensiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the LCSA consists of (a) environmental LCA, (b) life cycle costing, and (c) social life cycle assessment (SLCA; Kloepffer, 2008). However, the framework is currently in development and subsequently lacks the required empirical evidence to validate it as an effective measure of the social performance of a bio-based product (Falcone & Imbert, 2018).…”
mentioning
confidence: 99%
“…Falcone el al. (2018) reported on the trend toward ethical investing and socially responsible projects [25], whereby financial institutions are now making access to capital easier while venture capitalists find that green projects add value to companies. They found that there has also been a trend toward funding radical green innovation.…”
Section: Introductionmentioning
confidence: 99%